The Factors Influencing Purchase Intention by Students to Buy Counterfeit Products - Ponto, Riffat Verlila (2015)
Since there are many people in Indonesia that know and buy counterfeit products of CROCS and since this product is famous enough in society, the author wants to know the factors that can influence purchase intention by students to buy counterfeit products. The title of this research is The Factors Influencing Purchase Intention by Students to buy counterfeit products. The purpose of this research is to analyze the effect of brand personality, perceived product attributes, perceived benefits, product involvement and product knowledge toward purchase intention by students to buy counterfeit products. 125 respondents in this research are students of Muhammadiyah University of Surakarta. Technique sampling of research used was convenience sampling. The data in this research have fulfilled the normal distribution. The analysis results brand personality, product involvement and product knowledge were significant and supported while perceived product attributes and perceived benefits were not significant and not supported. Key words: Brand personality, Perceived product attributes, Perceived benefits, product involvement, Product knowledge and Purchase Intention. Surakarta, 04 November 2014 Author, (Riffat Verlila Ponto)